The Theoretical Reflection of Islamo-Fascism and Darul Islam Movement in Indonesia - Al Chaidar; Teuku Syahrul Ansari; Irfan Iryadi; Dedy Tabrani (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2019)
This study regarding the theoretical reflection of Islam-fascism and Darul Islam movement in Indonesia. History of Islam in Indonesia is also the history of power struggle (caliphate) which has not been completed until now. At that time Islam respecting plurality and respect the existing culture. The spirit of pluralism and tolerance enforced developed with enriched intellectual repertoire. Increasingly repressive and hegemonic states, bulldoze people across ethnic, class, and layers. Political regimentation of Suharto's New Order devastated spirit of nationality and humanity. Therefore, the intellectuals and the elite of Islam must find a way out of the crises of social, economic, and political ideology today, so that no reform has stagnated, so that this nation does not disintegrate. Giddens called political "third way" to emphasize the "no rights without responsibilities". In the era of the Prophet of Islam, "no rights without responsibilities" that accentuated in the Medina Charter, which guarantees the freedom, equality and justice. In the Islamic era Cordova, Spain, spirit and conception" Medina Charter" that then make their community a pluralistic, cosmopolitan, multicultural and universal, so they are willing to learn and accept everything of value from the experiences of other communities.